Influence of age on postural sway during different dual-task conditions - Bergamin, Marco; Gobbo, Stefano; Zanotto, Tobia; Sieverdes, John C.; Alberton, Cristine L.; Zaccaria, Marco; Ermolao, Andrea (Frontiers in Aging Neuroscience, 2014)
Dual-task performance assessments of competing parallel tasks and postural outcomes are growing in importance for geriatricians, as it is associated with predicting fall risk in older adults. This study aims to evaluate the postural stability during different dual-task conditions including visual (SMBT), verbal (CBAT) and cognitive (MAT) tasks in comparison with the standard Romberg’s open eyes position (OE). Furthermore, these conditions were investigated in a sample of young adults and a group of older healthy subjects to examine a potential interaction between type of secondary task and age status. To compare these groups across the four conditions, a within-between mixed model ANOVA was applied. Thus, a stabilometric platform has been used to measure center of pressure velocity (CoPV), sway area (SA), antero-posterior (AP) and medio-lateral (ML) oscillations as extents of postural sway. Tests of within-subjects effects indicated that different four conditions influenced the static balance for CoPV (p<0.001), SA (p<0.001). Post-hoc analyses indicated that CBAT task induced the worst balance condition on CoPV and resulted in significantly worse scores than OE (-11.4%; p<0.05), SMBT (-17.8% p<0.01) and MAT (-17.8% p<0.01) conditions; the largest SA was found in OE, and it was statistically larger than SMBT (-27.0%, p<0.01) and MAT (-23.1%; p<0.01). The between-subjects analysis indicated a general lower balance control in the group of elderly subjects (CoPV p<0.001, SA p<0.002), while, the mixed model ANOVA did not detect any interaction effect between types of secondary task and groups in any parameters (CoPV p=0.154, SA p=0.125). Postural sway during dual-task assessments was also found to decrease with advancing age, however, no interactions between aging and types of secondary tasks were found. Overall, these results indicated that the secondary task which most influenced the length of sway path, as measured by postural stability was a simple verbal assignment.